How to Assess in vitro Probiotic Viability and the Correct Use of Neutralizing Agents - Grispoldi, Luca; Giglietti, Riccardo; Traina, Giovanna; Cenci-Goga, Beniamino (Frontiers in Microbiology, 2020)
Probiotic viability is generally determined by quantifying the resistance to simulated gastric juice or to simulated intestinal fluid in in vitro tests, which measure microbial survival after given periods of contact. The use of a neutralizing agent is needed to avoid a carry-over of gastric or intestinal juice into the culture media of the subsequent analysis, and to avoid any antimicrobial effect extended over the defined period of contact of the test. Neutralization of gastric juice and intestinal juice are of the utmost importance to present data accurately. Failing to do so determines a carry-over of bactericidal activity to the plates used for the enumeration, which further reduces the number of surviving cells. Examples of such incorrect adaptation of the test are available in literature. The purpose of this perspective stems from the discovery that many studies do not adhere to internationally recognized standards, e.g. EN 1040:2005 (1), to evaluate the basic, bactericidal activity of compounds, especially for the neutralization step.